Safety of Protected Carotid Artery Stenting in Patients with Severe Carotid Artery Stenosis and Carotid Intraplaque Hemorrhage - Yoon, W. (AJNR Am J Neuroradiol, 2012)
BACKGROUND AND PURPOSE: Carotid IPH can be detected with MR imaging. The aim of this study was to determine the safety of CAS using an emboli protection device in patients with severe carotid artery stenosis and MR imaging–depicted carotid IPH. MATERIALS AND METHODS: We retrospectively reviewed a prospective data base that included 91 consecutive patients with severe carotid stenosis and high-risk features who were treated with CAS by using an emboli protection device. Seventy-eight of the included patients underwent prestenting 3D TOF MRA. IPH was defined as the presence of high signal intensity within the carotid plaque, greater than 150% of the signal intensity of the adjacent neck muscle on TOF source images. The primary outcome measure was the combined incidence of stroke, MI, and death within 30 days of CAS. Associations between IPH and the primary outcome were investigated. RESULTS: IPH was detected on TOF MRA in 30 patients. Symptomatic patients were more common in the IPH group than in the non-IPH group (66.7% vs 41.7%; P = .032). Overall, 30-day stroke, MI, or death rates were 6.6%. There was no significant difference in the primary outcome between the IPH and non-IPH groups (10% and 6.25%, respectively; hazard ratio for IPH, 1.151; 95% CI, 0.035 to 37.500; P = .937). A logistic regression showed there was no independent variable associated with the primary outcome. CONCLUSIONS: The results of this study indicate that protected CAS seems to be safe in patients with severe carotid stenosis and IPH.